Hands- on microsoft SQL Server 2005 Integration services - Nanda, Ashwani (McGraw hill, 2007)
Learn to maximize the features of SQL Server 2005 Integration Services from this essential guide. Hands-On Microsoft SQL Server 2005 Integration Services makes learning SSIS easy through the use of extensive real-world exercises structured around every component within the tool. You will learn to collect corporate data from various sources and transform that data for analysis, mining, and reporting.